Factors influencing the use of Google Classroom for lessons during Covid-19 pandemic among secondary ESL instructors / Mohd Haniff Mohd Tahir ... [et al.] - Mohd Tahir, Mohd Haniff; Mohd Adnan, Airil Haimi; Piaralal, Shushma Devi; Mohamad Shah, Dianna Suzieanna; Ya Shak, Mohamad Syafiq (2021)
Due to COVID-19, the education has transformed its mean of delivery from face to face to online lessons. This study evaluates the factors influencing Google Classroom (GC) use for lessons during COVID-19 pandemic among secondary ESL instructors in four northern states located in Peninsula Malaysia. A non-experimental research design was employed. Primary data collected from a self-administered online survey questionnaire are analysed descriptively in a general survey of trends, involving 103 survey respondents (i.e., teachers). The results of this study will help the stakeholders in Malaysian education to understand the factors affecting the use of GC at schools to make relevant decisions on its use among teachers. Besides, it will assist the Ministry of Education Malaysia to formulate policies related to the use of GC and assist secondary school administrators to make decisions on the type of infrastructure and technical support needed. A longitudinal study which included training programmes is recommended to assess the factors affecting GC used for instructions as such study will indicate whether longer instructions period results in better use of GC or not. This research extends value in the field of teachers’ instructions because it can be used to carry out further investigations in improving the use of GC among teachers. A possible global extension of this study should be conducted to further determine the power of GC instructions or other virtual instruction platforms in advancing virtual instruction prowess